A new atypical splice mutation in PKD2 leading to autosomal dominant polycystic kidney disease in a Chinese family - Junlin Zhang; Yiting Wang; Yingwang Zhao; Fang Liu (Singapore Medical Journal)
Introduction: Autosomal dominant polycystic kidney disease (ADPKD) is a very common hereditary renal disorder. Mutations in PKD1 and PKD2, identified as disease-causing genes, account for 85% and 15% of the ADPKD cases, respectively. Methods: In this study, the mutation analysis of polycystic kidney disease (PKD) genes was performed in a Chinese family with suspected ADPKD using targeted clinical exome sequencing (CES). The candidate pathogenic variants were further tested by using Sanger sequencing and validated for co-segregation. In addition, reverse transcription-polymerase chain reaction (RT-PCR) was performed to test for abnormal splicing and assess its potential pathogenicity. Results: A novel atypical splicing mutation that belongs to unclassified variants (UCVs), IVS6+5G>C, was identified in three family members by CES and was shown to co-segregate only with the affected individuals. The RT-PCR revealed the abnormal splicing of exon 6, which thus caused truncating mutation. These findings suggested that the atypical splice site alteration, IVS6+5G>C, in the PKD2 gene was the potential pathogenic mutation leading to ADPKD in this Chinese family. Conclusion: The data available in this study provided strong evidence that IVS6+5G>C is the potential pathogenic mutation for ADPKD. In addition, our findings emphasised the significance of functional analysis of UCVs and genotype–phenotype correlation in ADPKD.